Comparing Methods of Identifying Outlying Nurses in Audits of Low-Risk Cesarean Delivery Rates. Issue 2 (24th April 2022) - Edmonds, Joyce K.; Woodbury, Samuel R.; Lipsitz, Stuart R.; Weiseth, Amber; Farrell, Maureen E.; Shah, Neel T.; Greene, Naomi; Gregory, Kimberly D.
Abstract : Background: The low-risk cesarean delivery (CD) rate is an established performance indicator for providers in maternity care for quality improvement purposes. Purpose: Our objectives were to assess nurse performance using adjusted nurse-level CD rates and to compare methods of identifying nurse outliers. Methods: We conducted a retrospective, cohort study of 6970 births attended by 181 registered nurses in one hospital's maternity unit. Adjusted and unadjusted nurse-level CD rates were compared and agreement between 3 definitions (statistical, top decile, over a benchmark) of outliers calculated. Results: Adjusted nurse-level CD rates varied from 5.5% to 53.2%, and the unadjusted rates varied from 5% to 50%. Risk adjustment had little impact on the ranking of nurses, and outliers were consistently identified by 3 definitions. Conclusions: Trade-offs between statistical certainty and feasibility need to be considered when classifying nurse outliers. Findings can help target interventions to improve nurse performance.